HIV and substance use stigma, intersectional stigma and healthcare among HIV-positive PWID in Russia - Vetrova, Marina V. (AIDS Behav, 2021)
Little is known about the intersection of HIV stigma and substance use stigma. Using data from 188 HIV-positive people who inject drugs (PWID) in Russia, we examined the associations of these stigmas and their interaction with access and utilization of healthcare. While substance use stigma was significantly associated with poor access to care (AOR 2.31, 95%CI 1.50–3.57), HIV stigma was not. HIV stigma was associated with lower inpatient care utilization (AOR 0.32, 95%CI 0.14–0.65), while substance use stigma was not. We did not detect a significant interaction between the two forms of stigma for either of the primary outcomes. However, those with high levels of both substance use stigma and HIV stigma had higher odds of poor general access to healthcare (AOR 1.86, 95%CI 1.19–2.92), and lower odds of recent general outpatient (AOR 0.52, 95%CI 0.32–0.85) and any inpatient (AOR 0.48, 95%CI 0.22–0.99) care utilization compared to those with low levels of both types of stigma. Interventions addressing both substance use and HIV stigma in general healthcare settings might improve care in this HIV key population.